Hydroclimatic changes in the British Isles through the Last-Glacial-Interglacial Transition: Multiproxy reconstructions from the Vale of Pickering, NE England. (1st December 2020) - Lincoln, Paul C.; Matthews, Ian P.; Palmer, Adrian P.; Blockley, Simon P.E.; Staff, Richard A.; Candy, Ian
Abstract: European paleoenvironmental records through the Last Glacial-Interglacial Transition (LGIT; ca 16-8 cal ka BP) record a series of climatic events occurring over decadal to multi-centennial timescales. Changes in components of the climatic system other than temperature (e.g. hydrology) through the LGIT are relatively poorly understood however, and further records of hydroclimatic changes are required in order to develop a more complete understanding on the phasing of environmental and anthropogenic responses in Europe to abrupt climate change. Here, we present a multiproxy palaeoenvironmental record (macroscale and microscale sedimentology, macrofossils, and carbonate stable isotopes) from a palaeolake sequence in the Vale of Pickering (VoP), NE England, which enables the reconstruction of hydroclimatic changes constrained by a radiocarbon-based chronology. Relative lake-level changes in the VoP occurred in close association (although not necessarily in phase) to threshold shifts across abrupt climate change transitions, most notably lowering during cooling intervals of the LGIT (∼GI-1d, ∼GI-1b, and ∼GS-1). This reflects more arid hydroclimates associated with these cooling episodes in the British Isles. Comparisons to hydrological records elsewhere in Europe show a latitudinal bifurcation, with Northern Europe (50–60°N) becoming more arid (humid), and Southern Europe (40–50°N) becoming more humid (arid) in response to these cooling (warming) intervals. We attribute these bifurcating signals to the relative positions of the Atlantic storm tracks, sea-ice margin, and North Atlantic Polar Front (NAPF) during the climatic events of the LGIT. Highlights: Lake-level reconstructions can be used to reconstruct hydroclimatic changes. Northern (Southern) Europe becomes more arid (humid) during abrupt cooling events. European hydroclimatic changes were more dynamic than changes in temperature. Hydroclimatic changes were not concurrent with δ18O in the Greenland ice cores.